(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: This study delves into the comparison, recognizing the significance of effective management in preventing complications. Poor management of 3rd stage can lead to retained placenta, excessive bleeding, and increased maternal morbidity. Addressing these concerns, the research aims to contribute valuable insights for enhancing obstetric care and reducing adverse outcomes associated with inadequate management during this critical phase of childbirth. The Study aims to Determine the mean duration of 3rd stage of labor with oral misoprostol versus intramuscular oxytocin. A Prospective Comparative Study. This study was conducted at the Department of Gynecology and Obstetrics, Khair-Un -Nisa Hospital Lahore, Lahore over 12 months period from January 2022 to December 2022. Material and Methods: A total of 100 pregnant women meeting inclusion criteria were included in the study and divided into two equal groups using lottery method. Patients in Group A received oral misoprostol 600µg (3tablets of 200µg) and patients in Group B received 10 units intramuscular oxytocin. Labor process was managed as per standard protocol. All the findings were noted in a predesigned proforma and analyzed using SPSS version 27.0. Results: Mean age of the patients in this study was 25.92±4.55 years. In the study sample 40.0% women were primiparas whereas 60.0% were multiparas. Comparison of both the groups with regard to baseline characteristic produced insignificant difference between the groups (p-value>0.05). Mean duration of 3rd stage of labor was significantly high in group A than group B (4.98±0.82 vs. 3.72±0.80 min; p-value=0.000) and its stratification for age, parity and gestational age. Conclusion: In conclusion, our study reveals a significantly prolonged mean duration of the third stage of labor in the oral misoprostol group compared to the intramuscular oxytocin group. This difference persists across age, parity, and gestational age subgroups, emphasizing the robustness of these findings and contributing insights into intervention efficacy.